Wolbachia 16S rRNA haplotypes detected in wild Anopheles stephensi in eastern Ethiopia - Elizabeth Waymire; Sowmya Duddu; Solomon Yared; Dejene Getachew; Dereje Dengela; Sarah R. Bordenstein; Meshesha Balkew; Sarah Zohdy; Seth R. Irish; Tamar E. Carter (Parasites & Vectors, 2022)
Abstract Background About two out of three Ethiopians are at risk of malaria, a disease caused by the parasites Plasmodium falciparum and Plasmodium vivax. Anopheles stephensi, an invasive vector typically found in South Asia and the Middle East, was recently found to be distributed across eastern and central Ethiopia and is capable of transmitting both P. falciparum and P. vivax. The detection of this vector in the Horn of Africa (HOA) coupled with widespread insecticide resistance requires that new methods of vector control be investigated in order to control the spread of malaria. Wolbachia, a naturally occurring endosymbiotic bacterium of mosquitoes, has been identified as a potential vector control tool that can be explored for the control of malaria transmission. Wolbachia could be used to control the mosquito population through suppression or potentially decrease malaria transmission through population replacement. However, the presence of Wolbachia in wild An. stephensi in eastern Ethiopia is unknown. This study aimed to identify the presence and diversity of Wolbachia in An. stephensi across eastern Ethiopia. Methods DNA was extracted from An. stephensi collected from eastern Ethiopia in 2018 and screened for Wolbachia using a 16S targeted PCR assay, as well as multilocus strain typing (MLST) PCR assays. Haplotype and phylogenetic analysis of the sequenced 16S amplicons were conducted to compare with Wolbachia from countries across Africa and Asia. Results Twenty out of the 184 mosquitoes screened were positive for Wolbachia, with multiple haplotypes detected. In addition, phylogenetic analysis revealed two superclades, representing Wolbachia supergroups A and B (bootstrap values of 81 and 72, respectively) with no significant grouping of geographic location or species. A subclade with a bootstrap value of 89 separates the Ethiopian haplotype 2 from other sequences in that superclade. Conclusions These findings provide the first evidence of natural Wolbachia populations in wild An. stephensi in the HOA. They also identify the need for further research to confirm the endosymbiotic relationship between Wolbachia and An. stephensi and to investigate its utility for malaria control in the HOA. Graphical Abstract